Contextual risk and psychosocial profiles of opioid-using mothers: A mixed-methods study - Karina Beltrán-Arzate (SAGE Publishing, 2021)
Introduction: There is an increase in cases of mothers using opioids during pregnancy in the United States but research investigating mothers’ psychosocial environments along with individual variability among this high-risk group of women is scarce. Methods: This mixed-methods study aims to examine the complex interplay of contextual risks and experiences of opioid-using mothers. A sample of 50 opioid-using biological mothers of infants diagnosed with neonatal opioid withdrawal syndrome (NOWS) were studied using a set of standardized and open-ended questions, along with medical records extraction. Results: A high-risk subgroup of 36 mothers was identified using cluster analysis, characterized by a distinct profile of psychosocial risk. Thematic content analysis revealed four themes: (1) barriers to communication and mistrust of health professionals, (2) limitations of access to health care and the amplification of disadvantages related to COVID-19, (3) lifelong consequences of adverse childhood experiences (ACEs), and (4) intimate partner violence and its influence on drug use. Conclusion: Our findings highlight important information toward health services provision for opioid-using women of childbearing age. Efforts to reduce opioid usage in mothers need to consider psychosocial and contextual risks.